Regular Expressions - Pocket Primer - Campesato, Oswald (Pocket Primer, 2019)
As part of the best-selling Pocket Primer series, this book is meant to familiarize readers with regular expressions as part of their data-related tasks. Regular expressions (regex) are used in search engines, search and replace dialogs of word processors and text editors, in text processing utilities such as sed and awk, and in lexical analysis. Many programming languages provide regex capabilities, either built-in or via libraries. Readers will learn how to use bash commands grep, awk, and sed in order to use regular expressions in conjunction with datasets and data-related tasks.